Temporal analysis of ectopic enamel production in incisors from sprouty mutant mice - Boran, Tomas; Peterkova, Renata; Lesot, Herve; Lyons, David B; Peterka, Miroslav; Klein, Ophir D (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2009)
The mouse incisor has two unusual features: it grows continuously and it is covered by enamel exclusively on the labial side. The continuous growth is driven in part by epithelial stem cells in the cervical loop region that can both self-renew and give rise to ameloblasts. We have previously reported that ectopic enamel is found on the lingual side of the incisor in mice with loss-of-function of sprouty (spry) genes. Spry2(+/-); Spry4(-/-) mice, in which three sprouty alleles have been inactivated, have ectopic enamel as a result of upregulation of epithelial-mesenchymal FGF signaling in the lingual part of the cervical loop. Interestingly, lingual enamel is also present in the early postnatal period in Spry4(-/-) mice, in which only two sprouty alleles have been inactivated, but ectopic enamel is not found in adults of this genotype. To explore the mechanisms underlying the disappearance of lingual enamel in Spry4(-/-) adults, we studied the fate of the lingual enamel in Spry4(-/-) mice by comparing the morphology and growth of their lower incisors with wild type and Spry2(+/-); Spry4(-/-) mice at several timepoints between the perinatal period and adulthood. Ameloblasts and enamel were detected on the lingual side in postnatal Spry2(+/-); Spry4(+/-) incisors. By contrast, new ectopic ameloblasts ceased to differentiate after postnatal day 3 in Spry4(-/-) incisors, which was followed by a progressive loss of lingual enamel. Both the posterior extent of lingual enamel and the time of its last deposition were variable early postnatally in Spry4(-/-) incisors, but in all Spry4(-/-) adult incisors the lingual enamel was ultimately lost through continuous growth and abrasion of the incisor.
Keywords: Embryonic Development; ústní sliznice; membránové proteiny; Mouth Mucosa; genotyp; Membrane Proteins; Ameloblasts; Genotype; adaptorové proteiny signální transdukční; protein-serin-threoninkinasy; řezáky; Mice; Intracellular Signaling Peptides and Proteins; myši knockoutované; Nerve Tissue Proteins; Mice, Mutant Strains; mutantní kmeny myší; Protein Serine-Threonine Kinases; intracelulární signální peptidy a proteiny; zvířata; ameloblasty; Adaptor Proteins, Signal Transducing; proteiny nervové tkáně; embryonální vývoj; Mice, Knockout; myši; zubní sklovina; Dental Enamel; Incisor; Animals